Influence of bismuth oxide concentration on the pH level and biocompatibility of white Portland cement - Marina Angélica MARCIANO; Roberto Brandão GARCIA; Bruno Cavalini CAVENAGO; Paloma Gagliardi MINOTTI; Raquel Zanin MIDENA; Bruno Martini GUIMARÃES; Ronald ORDINOLA-ZAPATA; Marco Antonio Hungaro DUARTE (University of São Paulo, 2014)
Objectives: To investigate if there is a relation between the increase of bismuth oxide and the decrease of pH levels and an intensification of toxicity in the Portland cement. Material and Methods: White Portland cement (WPC) was mixed with 0, 15, 20, 30 and 50% bismuth oxide, in weight. For the pH level test, polyethylene tubes were filled with the cements and immersed in Milli-Q water for 15, 30 and 60 days. After each period, the increase of the pH level was assessed. For the biocompatibility, two polyethylene tubes filled with the cements were implanted in ninety albino rats (n=6). The analysis of the intensity of the inflammatory infiltrate was performed after 15, 30 and 60 days. The statistical analysis was performed using the Kruskal-Wallis, Dunn and Friedman tests for the pH level and the Kruskal-Wallis and Dunn tests for the biological analysis (p<0.05). Results: The results showed an increase of the pH level after 15 days, followed by a slight increase after 30 days and a decrease after 60 days. There were no significant statistical differences among the groups (p>0.05). For the inflammatory infiltrates, no significant statistical differences were found among the groups in each period (p>0.05). The 15% WPC showed a significant decrease of the inflammatory infiltrate from 15 to 30 and 60 days (p<0.05). Conclusions: The addition of bismuth oxide into Portland cement did not affect the pH level and the biological response. The concentration of 15% of bismuth oxide resulted in significant reduction in inflammatory response in comparison with the other concentrations evaluated.